The strategic advantage in the coffee market of family agriculture in Alto Paraíso de Goiás - Iara Campos, Jurema; Eduardo Farah Valente, Ana Lúcia (Coffee Science - ISSN 1984-3909, 2011)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>This work analyzes family farmers in the municipality of Alto Paraíso de Goiás, Goiás state, Brazil, in their search for alternative sources of income that will establish them in the market. The municipality was first settled in the sixteenth and seventeenth centuries by miners and has, since then, maintained an agricultural tradition. Economic activity changed in the 1960’s with the exploitation of tourism. However, the region’s history is one of poverty and stagnation. Tourism was the main economic activity until the early 2000’s, when diseases such as yellow fever were registered among tourists and the local population. The study was carried out using semi-structured questionnaires, applied to 28 farmers in the region. From an overall survey and assessment of rural life and development impairments, the aim of this work was to study the possibility of promoting the sustainable development of family coffee production units in the region. There are still old productive coffee trees (Coffea sp.) planted along rivers whose product is consumed by the local population and by tourists. Coffee was introduced in the region in the early eighteenth century by scout troops and is grown today by farmers who, after the decline of tourism, are searching for alternative sources of income allied to sustainable development. The conclusion is that these producers have intrinsic advantages for establishing a coffee production system that can be inserted into the specialty coffee niche markets. Therefore, to become a strategic advantage, small-scale production should be associated to local tradition, nature and handicraft, all of which are currently valued by the specialty coffee consumer market.